2018
DOI: 10.1111/hiv.12597
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of acute hepatitis A among young adult men: clinical features and HIV coinfection rate from a large teaching hospital in Rome, Italy

Abstract: In 2016-2017, we saw a rise in the number of hepatitis A cases, with a higher prevalence of adult male patients. No significant differences regarding the prevalence of HIV coinfection emerged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Germany (n=9) (16, 29, 32, 34, 37, 52, 56, 59, 62), Spain (n=8) (43-45, 48, 61, 63-65), Italy (n=6) (33, 36, 40, 46, 47, 58, 60) and Greece (n=5) (28, 42, 50, 51, 54, 55) were the countries that most frequently reported outbreaks involving migrants between 2000 and 2020. Two thirds (n=6) of included outbreaks in Germany affected refugee or asylum-seeking populations, mostly in temporary camps, 78% (n=7) were measles outbreaks and all but one were reported in 2010 or later.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Germany (n=9) (16, 29, 32, 34, 37, 52, 56, 59, 62), Spain (n=8) (43-45, 48, 61, 63-65), Italy (n=6) (33, 36, 40, 46, 47, 58, 60) and Greece (n=5) (28, 42, 50, 51, 54, 55) were the countries that most frequently reported outbreaks involving migrants between 2000 and 2020. Two thirds (n=6) of included outbreaks in Germany affected refugee or asylum-seeking populations, mostly in temporary camps, 78% (n=7) were measles outbreaks and all but one were reported in 2010 or later.…”
Section: Resultsmentioning
confidence: 99%
“…Eight papers included in this review reported on hepatitis A outbreaks involving migrants. Two papers reported on outbreaks occurring in Germany (24, 34), two in Spain (25, 43), two in Greece (28, 42) and one each in Ireland (41) and Italy (40). A total of 1,510 cases of hepatitis A were reported as part of outbreaks involving migrants, of which 1,322 (87.5%) occurred after January 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Germany (n=9) (18,31,34,36,39,54,58,61,64), Spain (n=8) (45-47, 50, 63, 65-67), Italy (n=6) (35,38,42,48,49,60,62) and Greece (n=5) (30,44,52,53,56,57) were the countries that most frequently reported outbreaks involving migrants between 2000 and 2020. Two thirds (n=6) of included outbreaks in Germany affected refugee or asylum-seeking populations, mostly in temporary camps, 78% (n=7) were measles outbreaks and all but one were reported in 2010 or later.…”
Section: Geographical Distribution Of Vpds: Spatial Mapping Analysismentioning
confidence: 99%
“…Up to now, most of the cases were connected with the consumption of contaminated water or food; virtually any food can be contaminated with HAV, especially food that is not properly heated after contamination (Lin et al., 2017). Low socioeconomic conditions and poor sanitation are considered to be important risk factors of infection (Ciccullo et al, 2018; Lin et al, 2017). The last outbreak in Europe and North America once again revealed that HAV should be considered a sexually transmitted infection (STI) via oral–anal sex, but also digito–anal and genito–oral sex.…”
mentioning
confidence: 99%
“…The last outbreak in Europe and North America once again revealed that HAV should be considered a sexually transmitted infection (STI) via oral–anal sex, but also digito–anal and genito–oral sex. Due to these sexual activities, men who have sex with men (MSM) are known to be a high-risk group (Boucher et al, 2018; Ciccullo et al, 2018; Lin et al, 2017; Ndumbi et al, 2017).…”
mentioning
confidence: 99%